Differences in the Effect of the Hello Drill and Glass Balance Training Programs on Backstroke Swimming Speed in Satria Muda Athletes from Sidoarjo Regency - Agustina Mahardika; Santika Hadi; Ismawandi Putra (Sinar Sport Journal, 2025)
Backstroke swimming often faces body balance challenges that cause trajectory deviation and decreased speed in adolescent athletes. This study aims to examine the differences in the effects of the Hello Drill and Glass Balance training programs on 50-meter backstroke swimming speed. Using a quantitative quasi-experimental approach with a two-group pretest-posttest design, a population of 20 Satria Muda athletes from Sidoarjo Regency aged KU3 (13-14 years) was divided into two equivalent groups (n=10). The speed test instrument was analyzed using the Kolmogorov-Smirnov normality test, Levene's homogeneity test, paired and independent t-test via SPSS 31 (α=0.05). The results showed that Hello Drill increased speed by 6.33% (45.25 to 42.39 seconds; p=0.004) and Glass Balance by 20.81% (45.25 to 35.83 seconds; p=0.001), with a significant difference between groups (p=0.043). Glass Balance is more effective because it optimizes body stability.